2022
DOI: 10.1097/gme.0000000000002053
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial microbiota from endometrial cancer and paired pericancer tissues in postmenopausal women: differences and clinical relevance

Abstract: Objectives: Assess acceptability of a 12-minute educational video before menopause clinic consultation and evaluate its impact on knowledge and treatment certainty.Methods: This was a pre-post intervention study among new patients with vasomotor symptoms (VMS) referred to a menopause clinic in Toronto, Canada. Participants completed electronic questionnaires before and after viewing a 12-minute online video covering menopause facts and VMS treatments. Participants' demographic information and referring provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Carcinogenesis may be able to cause local microbiome variation. Wang et al (127) revealed that endometrial cancer tissues differed significantly from the non-cancerous fraction of the microbiome, accompanied by elevated α diversity and enrichment of Prevotella, Atopobium, Anaerococcus, Dialister, Porphyromonas and Peptoniphilus, similar to the dysbiotic state of the vaginal flora (127). The differences in results are related to the method of tissue sampling and the magnitude of contamination potential, the scientific nature of which needs to be confirmed by numerous studies.…”
Section: Gynecological Cancer Microbiomementioning
confidence: 99%
“…Carcinogenesis may be able to cause local microbiome variation. Wang et al (127) revealed that endometrial cancer tissues differed significantly from the non-cancerous fraction of the microbiome, accompanied by elevated α diversity and enrichment of Prevotella, Atopobium, Anaerococcus, Dialister, Porphyromonas and Peptoniphilus, similar to the dysbiotic state of the vaginal flora (127). The differences in results are related to the method of tissue sampling and the magnitude of contamination potential, the scientific nature of which needs to be confirmed by numerous studies.…”
Section: Gynecological Cancer Microbiomementioning
confidence: 99%
“…The presence of Porphyromas somerae is the most predictive microbial marker of endometrial cancer and might be useful in detecting endometrial cancer in high-risk, asymptomatic women. Wang et al [ 38 ] revealed the significant differences between the paired endometrial cancer and adjacent non-endometrial cancer endometrial microbiota in their clinical study of 28 menopausal women who were histopathologically diagnosed with endometrioid adenocarcinoma, some of whom underwent hysterectomy using the open surgical approach.…”
Section: Changes In Vaginal Microbiota In Menopausal Womenmentioning
confidence: 99%
“…An alteration in the estrobolome (dysbiosis) and its regulatory functions leads to an imbalance of various biological processes, promoting the onset of pathologies such as cancer. Wang et al [89] observed a different microbiota in endometrial cancer (EC) tissues as compared to pericancer tissues. In particular, EC tissues were enriched in the genera Prevotella, Atopobium, Peptostreptococcus, Anaerococcus, Fastidiosipila, Finegoldia, DNF00809, Dialister, Peptoniphilus, Porphyromonas, Anaeroglobus, and Criibacterium, while an abundance of Lactobacillus is found in PC tissues [89].…”
Section: Microbiota and Endometrial Cancermentioning
confidence: 99%
“…Wang et al [89] observed a different microbiota in endometrial cancer (EC) tissues as compared to pericancer tissues. In particular, EC tissues were enriched in the genera Prevotella, Atopobium, Peptostreptococcus, Anaerococcus, Fastidiosipila, Finegoldia, DNF00809, Dialister, Peptoniphilus, Porphyromonas, Anaeroglobus, and Criibacterium, while an abundance of Lactobacillus is found in PC tissues [89]. Furthermore, a high abundance of Prevotella and high levels of D-dimer were observed in EC tissues, often correlating with disease severity and poor prognosis [90].…”
Section: Microbiota and Endometrial Cancermentioning
confidence: 99%